APLIKASI METODE TRANSPORT ROAD AND RESEARCH LABORATORY (TRRL) DALAM MENGANALISIS BESARAN TINGKAT KEBISINGAN LALULINTAS PADA JALAN M. T. HARYONO KOTA KENDARI (Studi Kasus : Simpang Ade Swalayan – Simpang Pasar Baru) - Susanti Djalante; Siti Nurjanah Ahmad (Fakultas Teknik Jurusan Sipil Universitas Halu Oleo, 2014)
AbstractThis paper aims to determine the traffic noise that occurs on the MT Haryono street (intersection from Ade Swalayan to Pasar Baru). The data was collected from traffic volume, vehicle speed, road gradient, sound source and building barrier. The method used for noise calculations is based on